The Effect of Group Counseling Services with S.F.B.C Approach on Increasing Adolescent Resilience - Ardi Kurniawan; Paramita Nuraini; Indiati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to examine the effect of group counseling services with the S.F.B.C approach on increasing adolescent resilience. This research is a type of pre-experimental research using the One Group Pretest Posttest Design. The design uses one group of subjects with one type of treatment, namely the experimental group. The population in this study were PAY Aisyiyah teenagers, totaling 22 teenagers. The number of samples in this study were 8 teenagers as the experimental group. Determination of the sample using random sampling. The data analysis method for hypothesis testing in this study used a non-parametric Paired sample t-test with the help of SPSS 25.0 for windows. The results of this study indicate that group counseling services with the S.F.B.C approach have a positive effect on increasing adolescent resilience. This is evidenced by the results of the paired sample t-test with a significant (2-tiled) probability of 0.000 <0.05. And based on the results of the analysis and discussion, there is a difference in the average score of the adolescent social responsibility questionnaire of 12.5% from the results of the pretest and posttest results of the adolescent resilience questionnaire.